Supporting Irish traveller entrepreneurship. Issue 1 (2nd January 2017) - Collins, Martin
ABSTRACT: Irish Travellers are a minority ethnic group, indigenous to the island of Ireland. Despite the recent historic ethnic recognition by our Taoiseach, Enda Kenny, Traveller participation in the labour market remains exceptionally low, with an overall unemployment rate of 84.3% reported in Census 2011. This article outlines some of the key barriers to Traveller labour market participation and argues that Traveller experiences of the labour market are rooted in and have been shaped by a legacy of racism and discrimination on individual, institutional and structural levels. It argues for a rapid policy response by the State and the development of long-term sustainable strategies to improve Traveller training and employment opportunities.